Research Note—Customer Loyalty Programs: Are They Profitable? - Singh, Siddharth S.; Jain, Dipak C.; Krishnan, Trichy V. (Management Science, 2008)
Loyalty programs are very common in practice. Many researchers have worked at understanding the impact of loyalty programs on market competition and the mechanism behind it. Interestingly, almost all of the studies have explored a symmetric equilibrium where both of the competing firms offer a loyalty program. To our knowledge, the extant literature has not investigated in-depth whether asymmetric equilibrium can exist where only one firm chooses to offer a loyalty program and the other firm chooses to compete via lowering prices. Such a question is important because some markets do support such asymmetric equilibriums with respect to loyalty programs. Also, the existence of asymmetric equilibrium shows that a loyalty program need not be profitable for some firms. In this paper, we use a game-theoretic framework to investigate specific types of customer loyalty programs that provide benefit to loyal customers in the form of discount over market prices. The model considers consumer switching and includes two types of consumer heterogeneity. The first type of heterogeneity concerns the differences between customers with respect to their liking for loyalty programs, and the second type concerns the differences among the loyalty program members with respect to their ability to collect enough loyalty points to redeem loyalty rewards. By analyzing a duopoly market, we find that both symmetric equilibrium (i.e., where both competing firms offer the loyalty program) and asymmetric equilibrium (i.e., where one firm alone offers the loyalty program) can be sustained. The paper explores conditions for the existence of these two equilibriums.